A QUALITY ASSURANCE FRAMEWORK FOR SULPHONIC ACID-COATED SAND USED IN 3D PRINTING APPLICATIONS - van Tonder, Malan; de Beer, Deon Johan; Wichers, Harry (The South African Journal of Industrial Engineering, 2020)
The need for companies to adopt a quality management strategy has significantly increased in recent times as a result of global competition and more demanding customers. It is important to integrate quality throughout the product lifecycle, which includes the design phase. The purpose of the paper is to develop a quality assurance framework for the local production of chemical-coated sand used in the Voxeljet VX1000 printing process. The framework could be used as a basic structure to develop the necessary processes, procedures, and work instructions to ensure the quality of local chemical-coated sand.